2017
DOI: 10.1021/acs.accounts.7b00306
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Tethered Strategies for C–H Functionalization Reactions

Abstract: CONSPECTUS Selective and efficient functionalization of ubiquitous C–H bonds is the Holy Grail of organic synthesis. Most advances in this area rely on employment of strongly or weakly coordinating directing groups (DGs) which have proven effective for transition-metal-catalyzed functionalization of C(sp2)–H and C(sp3)–H bonds. Although most directing groups are important functionalities in their own right, in certain cases, the DGs become static entities that possess very little synthetic leverage. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(42 citation statements)
references
References 66 publications
(103 reference statements)
0
42
0
Order By: Relevance
“…Following this general concept several research groups entered the field of Si-based DGs in C–H functionalisation. 735 , 1090 , 1091 Already more than one decade ago several research groups questioned the potential of “SiR 2 H” to play a double role of a DG to drive the C–H activation event at one specific position and to provide, in an intramolecular fashion, a silicone-based coupling partner. The potential of such reactions holds also a major synthetic value as the newly formed C–Si bonds might be further interconverted into several functionalised motifs.…”
Section: Other Dgs Employed In C–h Functionalisationmentioning
confidence: 99%
“…Following this general concept several research groups entered the field of Si-based DGs in C–H functionalisation. 735 , 1090 , 1091 Already more than one decade ago several research groups questioned the potential of “SiR 2 H” to play a double role of a DG to drive the C–H activation event at one specific position and to provide, in an intramolecular fashion, a silicone-based coupling partner. The potential of such reactions holds also a major synthetic value as the newly formed C–Si bonds might be further interconverted into several functionalised motifs.…”
Section: Other Dgs Employed In C–h Functionalisationmentioning
confidence: 99%
“…In fact, only intramolecular C−H bond functionalization approaches have been reported to access cyclic silicon‐stereogenic silanes such as dibenzosiloles and 5,10‐dihydrophenazasiline, including the direct arylation, dehydrogenative silylation, 1,5‐palladium migration reaction, and ring expansion/dehydrogenative silylation reactions. The pioneering work by the group of Gevorgyan showed that pyridine and pyrimidine serve as powerful directing groups in various C−H functionalization reactions of silicon‐tethered arenes (Scheme ). However, to the best of our knowledge, there have been no successful examples on the transition‐metal‐catalyzed intermolecular C−H functionalization of prochiral organosilicon compounds which allow for the synthesis of acyclic silicon‐stereogenic tetraorganosilicons with heteroatom‐containing functional groups.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, only intramolecular CÀHb ond functionalization approaches have been reportedt oa ccess cyclic siliconstereogenic silanes such as dibenzosiloles and 5,10-dihydrophenazasiline, including the direct arylation, [7] dehydrogenative silylation, [8] 1,5-palladium migration reaction, [9] and ring expansion/dehydrogenative silylation [10] reactions. The pioneering work by the group of Gevorgyan showedt hat pyridine and pyrimidine serve as powerful directing groups in various CÀH functionalization reactions of silicon-tethered arenes [11] (Scheme 1). However,t ot he best of our knowledge, there have been no successful exampleso nt he transition-metal-catalyzed intermolecular CÀHf unctionalization of prochiral organosilicon compounds which allow for the synthesis of acyclic silicon-stereogenic tetraorganosiliconsw ith heteroatom-containingf unctional groups.I nspired by the findings that amino acid can promote the ortho-CÀHa ctivation of phenols with a silicon-tetheredd irectingg roup [12] (Scheme 1a)a nd the MPAA/ Pd complexesa re efficient catalysts for the syntheses of P-and S-chiral compounds [13] via CÀHa ctivation,w ee nvisioned that silicon-stereogenic certers may be produced via desymmetric CÀHf unctionalization of one of two identical aryls at the prochiral silicon under chiral palladium complex catalysis.…”
mentioning
confidence: 99%
“…[12,13] Thesilyl group adds transiently to the metal center and can be used after the borylation reaction to create ar ange of functional groups by transformations that are orthogonal in most cases to those of the transformations of CÀ Bb onds,thus largely increasing the product diversity. [12,13] Thesilyl group adds transiently to the metal center and can be used after the borylation reaction to create ar ange of functional groups by transformations that are orthogonal in most cases to those of the transformations of CÀ Bb onds,thus largely increasing the product diversity.…”
mentioning
confidence: 99%
“…Our group has reported silyl-directed borylations of C À H bonds,i nw hich the borylation occurred at aromatic C À H bonds or C(sp 3 ) À Hbonds ortho to asubstituent containing an SiÀHbond. [12,13] Thesilyl group adds transiently to the metal center and can be used after the borylation reaction to create ar ange of functional groups by transformations that are orthogonal in most cases to those of the transformations of CÀ Bb onds,thus largely increasing the product diversity. [12] We report the peri-borylation of C À Hb onds in 1-hydrosilyl naphthalenes and related polyaromatic hydrocarbons (Scheme 1d).…”
mentioning
confidence: 99%